The Human and Economic Implications of Twenty-First Century Immigration Policy - Pozo, Susan (W.E. Upjohn Institute, 2023)
To effectively debate immigration policy we need to be better informed. This book helps by presenting a group of prominent scholars who use data to help unravel the facts. They address immigration’s fiscal impacts, immigrants’ generational assimilation, enhanced U.S. enforcement, and alternatives for those seeking refugee status. Together, they help move us from the personal to the analytical, providing us a rational appraisal of immigration and the policies currently before us.